Synthesis and electrochemistry of diels-alder adducts of [60]fulierene with a phthalocyanine and a hemiporphyrazine - Dürr, Kai; Fiedler, Stefan; Linßen, Torsten; Hirsch, Andreas; Hanack, Michael (Chemische Berichte, 1997)
The synthesis of a new Diels-Alder adduct 7 of [60]fullerene and a phthalocyaninenickel compound containing a longer spacer than the originally reported Diels-Alder adduct 1 is described. The bisenophilic hemiporphyrazinenickel compound 11 reacts with [60]fullerene to form a Diels-Alder adduct 12 containing two fullerene units. Spectroelectrochemi-cal investigations of 7 and 12 reveal multiple reductions, which are attributed to the corresponding subunits of the molecules. In contrast to 1, the electron acceptor properties of the [60]fullerene unit in both molecules have no influence on the electronic properties of the phthalocyanine and herniporphyrazine, respectively. © WILEY-VCH Verlag GmbH.